Editorial: mHealth tools for patient empowerment and chronic disease management - Sousa, Pedro (2023)
Modern societies are facing new healthcare challenges with the integration of digital health interventions as a part of their healthcare systems. However, the digital transformation of healthcare requires active patient engagement as a core component of healthcare interventions. In the case of chronic diseases, new digital tools are believed to help maintain and improve patient health and care, by optimizing the course of disease treatment. Indeed, facilitating access to quality health services and building the capacity to reduce risk are key priorities around the world. Nevertheless, health systems are facing unprecedented financial pressures at a time of growing demand for their services. Technology can help people use care services less by promoting healthier lives. Prompt advances in wearable sensor technologies and mobile communications could close the gap between home- and clinic-based care delivery models by linking accessibility, availability, and responsive, tailored clinical oversight. Digital health solutions can help democratize access to medical care. Even though mobile health (mHealth) tools are widely recognized as a promising resource capable of changing healthcare, additional research is needed to enhance knowledge about their limitations and benefits for chronic disease management and patient empowerment. Nota: Extrato retirado do corpo do artigo.